2018
DOI: 10.3892/mmr.2018.8635
|View full text |Cite
|
Sign up to set email alerts
|

DFMG reverses proliferation and migration of vascular smooth muscle cells induced by co-culture with injured vascular endothelial cells via suppression of the TLR4-mediated signaling pathway

Abstract: 7-Difluoromethoxy-5,4′-dimethoxy-genistein (DFMG) is a novel chemical compound synthesized using genistein. Previous studies have indicated that DFMG can reverse the apoptosis of vascular endothelial cells (VECs) by regulating the mitochondrial apoptosis pathway. The present study aimed to investigate the activity and molecular mechanism underlying DFMG-mediated protection of vascular smooth muscle cell (VSMCs) using a non-contact co-culture model established by using Transwell insert. Secretion of interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
0
8
2
Order By: Relevance
“… 56 , 61 In addition, it has been reported that lysoPC can promote the expression of IL-1β and secretion of IL-6 and TNF-α in endothelial cells in vitro. 8 , 36 However, we observed a negative correlation between IL-6 and lysoPC 26:0, contradicting what was observed in those in vitro studies. 8 , 37 In vivo studies are needed to verify the role of lysoPCs in regulating cytokine expression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 56 , 61 In addition, it has been reported that lysoPC can promote the expression of IL-1β and secretion of IL-6 and TNF-α in endothelial cells in vitro. 8 , 36 However, we observed a negative correlation between IL-6 and lysoPC 26:0, contradicting what was observed in those in vitro studies. 8 , 37 In vivo studies are needed to verify the role of lysoPCs in regulating cytokine expression.…”
Section: Discussioncontrasting
confidence: 99%
“… 8 , 36 However, we observed a negative correlation between IL-6 and lysoPC 26:0, contradicting what was observed in those in vitro studies. 8 , 37 In vivo studies are needed to verify the role of lysoPCs in regulating cytokine expression.…”
Section: Discussioncontrasting
confidence: 99%
“…ECs dysfunction promotes AD development through pro-inflammatory effect 14. VSMC dysfunction can be stimulated by endothelial injury signals, and participates in the pathogenesis of vascular diseases 49. This study revealed that EC apoptosis was essential for AD in response to suppression of miR-27a.…”
Section: Discussionmentioning
confidence: 81%
“…There is limited literature available on flavonoids and their effects on vascular regeneration; however, one of the isoflavone present in legumes, genistein, can eliminate free radicals, and boost antioxidant enzyme activities when combined with 7-difluoromethoxy-5′4-dimethoxy (DFMG). This novel antioxidant compound effectively inhibits VSMCs proliferation and migration by regulating the Toll-like receptor-4 (TLR4) signaling pathway as well as reducing oxidative stress (59) and endothelial cell impairment (60). These studies suggest that genistein may possibly prevent vascular disorders by restoring vascular function and promoting vascular cell regeneration.…”
Section: The Impact Of Natural Antioxidants On the Regeneration Potenmentioning
confidence: 99%